Worsening of Preexisting Psychiatric Conditions During the COVID-19 Pandemic - Gobbi, Susanna; Płomecka, Martyna Beata; Ashraf, Zainab; Radziński, Piotr; Neckels, Rachael; Lazzeri, Samuel; Dedić, Alisa; Bakalović, Asja; Hrustić, Lejla; Skórko, Beata; Es haghi, Sarvin; Almazidou, Kristina; et al. (Frontiers in Psychiatry, 2020)
Objectives: To ascertain factors associated with worsening of psychiatric conditions during the COVID-19 pandemic. Methods: This study anonymously examined 2,734 psychiatric patients worldwide for worsening of their pre-existing psychiatric condition during the COVID-19 pandemic. An independent clinical investigation of 318 psychiatric patients from USA was used for verification. Results: Valid responses mainly from 12 featured countries indicated self-reported worsening of psychiatric conditions in 2/3rd of the patients assessed that was validated through their significantly higher scores on scales for general psychological disturbance, post-traumatic stress disorder, and depression. Female gender, feeling no control of the situation and reporting dissatisfaction with the response of the state during the COVID-19 pandemic, and reduced interaction with family and friends increased the worsening of pre-existing psychiatric conditions, whereas optimism, ability to share concerns with family and friends and using social media like usual were associated with less worsening. An independent clinical investigation from the USA confirmed worsening of psychiatric conditions during the COVID-19 pandemic based on identification of new symptoms that necessitated clinical interventions such as dose adjustment or starting new medications in more than half of the patients. Conclusions: More than half of the patients are experiencing worsening of their psychiatric conditions during the COVID-19 pandemic.